Butterfly genome reveals promiscuous exchange of mimicry adaptations among species - Dasmahapatra, Kanchon K (2012)
The evolutionary importance of hybridization and introgression has long been debated(1). We used genomic tools to investigate introgression in Heliconius, a rapidly radiating genus of neotropical butterflies widely used in studies of ecology, behaviour, mimicry and speciation(2-5) . We sequenced the genome of Heliconius melpomene and compared it with other taxa to investigate chromosomal evolution in Lepidoptera and gene flow among multiple Heliconius species and races. Among 12,657 predicted genes for Heliconius, biologically important expansions of families of chemosensory and Hox genes are particularly noteworthy. Chromosomal organisation has remained broadly conserved since the Cretaceous, when butterflies split from the silkmoth lineage. Using genomic resequencing, we show hybrid exchange of genes between three co-mimics, H. melpomene, H. timareta, and H. elevatus, especially at two genomic regions that control mimicry pattern. Closely related Heliconius species clearly exchange protective colour pattern genes promiscuously, implying a major role for hybridization in adaptive radiation.